Empowering peace: service provision and state legitimacy in Nepal's peace-building process. Issue 1 (2nd January 2016) - Krampe, Florian
Abstract: There is growing demand for an understanding of peace beyond the absence of violence. As such research focuses increasingly on the issue of state legitimacy as a tool to assess and understand peace processes. In this paper the relationship between service provision and state legitimacy is studied to assess whether the provision of services like electricity to rural communities of war-torn countries through state actors contributes to the consolidation of the post-war political system. The qualitative analysis of two localities in post-war Nepal highlights that service provision in the form of electricity through micro-hydropower yields tremendously positive socio-economic effects for rural communities. However, socio-economic development in combination with interactions among villagers has strengthened local autonomy through emphasising alternative local governance structures. This highlights that the relationship between service provision and state legitimacy is more complex than previous research anticipates. The absence of a positive effect on state legitimacy raises the question of whether in its current case-specific form service provision is conducive to the broader peace-building efforts in post-war Nepal, because it stresses the divide between state and society.